2015
DOI: 10.1371/journal.pone.0129648
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Evolution and Blast Crisis Correlate with Enhanced Proteolytic Activity of Separase in BCR-ABL b3a2 Fusion Type CML under Imatinib Therapy

Abstract: Unbalanced (major route) additional cytogenetic aberrations (ACA) at diagnosis of chronic myeloid leukemia (CML) indicate an increased risk of progression and shorter survival. Moreover, newly arising ACA under imatinib treatment and clonal evolution are considered features of acceleration and define failure of therapy according to the European LeukemiaNet (ELN) recommendations. On the basis of 1151 Philadelphia chromosome positive chronic phase patients of the randomized CML-study IV, we examined the incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
3
11
0
Order By: Relevance
“…In search for transcriptional mechanisms that could explain the IM-associated downregulation of Separase protein levels we analyzed the conditional context between c-MYB expression, Separase and IM treatment. Confirming and expanding previously published work we performed cell culture experiments on four human cell lines [ 13 , 35 ]. Of these, U937 cells served as model for leukemic but BCR-ABL-negative cells.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…In search for transcriptional mechanisms that could explain the IM-associated downregulation of Separase protein levels we analyzed the conditional context between c-MYB expression, Separase and IM treatment. Confirming and expanding previously published work we performed cell culture experiments on four human cell lines [ 13 , 35 ]. Of these, U937 cells served as model for leukemic but BCR-ABL-negative cells.…”
Section: Resultssupporting
confidence: 73%
“…Recently, we have reported that enhanced rates of acquired chromosomal aberrations, clonal evolution and fast disease progression (time to BC) in CML patients undergoing long-term IM treatment correlate with enhanced proteolytic activity of Separase in the respective in vitro models [ 35 ]. Mechanistically, this was linked to a BCR-ABL-dependent regulatory feedback mechanism that posttranslationally stimulates Separase proteolytic activity after IM-induced decreases of Separase expression in b3a2 BCR-ABL fusion type CML cell lines [ 35 ]. To date, it was unclear what underlying transcriptional or translational mechanism may be involved in the IM-dependent regulation of Separase expression in BCR-ABL-positive cells.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we found that the posttranslationally stimulated separase proteolytic activity under imatinib treatment rendered b3a2 fusion type-related CML cells more prone to aneuploidy and clonal evolution, thereby confirming cytogenetic findings within a cohort of 1151 Philadelphia chromosome-positive chronic phase patients of the randomized CML-study IV that were examined on the incidence of newly arising additional chromosomal alterations (ACAs) under prolonged imatinib treatment. This points to an influence of high separase activity for the induction of gross genomic mutations in CML cells [30].…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, unscheduled (cell cycle uncoupled) activation of separase can lead to aberrant high numbers of centrosomes (i.e., centrosome amplification) and subsequently to a defective mitotic spindle apparatus [25]. Both defects cause the emergence of aberrant karyotypes (aneuploidy), a hallmark of most advanced human malignancies [24,[26][27][28][29][30]. Overexpression of separase in the mammary gland of a MMTV-ESPL1 mouse model led to the development of highly aneuploid mammary carcinomas with high levels of chromosomal instability and aggressive disease phenotypes [31].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of separase in transgenic MMTV-Espl1 mouse model leads to aggressive mammary adenocarcinomas with an 80% penetrance [Mukherjee et al, 2014b]. Around 5.4-fold increase in separase activity under imatinib treatment was observed in b3a2 cell lines [Haaß et al, 2015a]. Mutation in separase leads to increased genetic instability and predisposition to epithelial cancer in zebrafish [Shepard et al, 2007].…”
Section: Separase As Oncogenementioning
confidence: 99%